Método de exposição e teoria revolucionária: considerações sobre a lógica dialética da revolução e o sentido político do livro I de O Capital , de Karl Marx - Paiva Neto, Antônio Corrêa de (2012)
The current paper has as a theme the configuration of the dialectical method in the First book of The Capital and, as essential problem, the question for the existence of a political meaning in the way of exhibition of the book. Its aim is to demonstrate that the exposed development of The Capital , structured according to the dialectical method, reflects a revolutionary theory. This theory can be understood, in other words, as a theory regarding the overcome of the way of capitalist production, propitiating, still, a consciousness systematization of the working class, and, thus, a perception from this class of the necessity of this economic system to be overcome, characterizing the book, on this meaning, as a political instrument focused on the revolutionary organization. Subdivided in three parts, the referred paper, on the first part, refers to the concept dialectic and its application on The Capital , on the second, it is about the negative-expositive movement of the work, presenting the determinations of the revolutionary theory and the political meaning of its expositive method; and finally, the third part, is of a controversy between Hector Benoit and Francisco Soares Teixeira regarding the way of exposition of the book. On this way, in general, it can be seen that Marx comprehends the dialectic as a method that consists in revealing not only the laws that govern the working of a specific object, but also the laws of its transition, being set in The Capital as an expositive method with the purpose not only to reveal the laws of working of the way of capitalist production, but also to the laws related to its necessary overcome. Reflecting the own way of exposition of The Capital , the movement of overcome of the capitalism, Marx would explicit that the revolutionary process is inherent in the development of the mentioned economic system, on which would be formed the objective and subjective assumptions for the constitution of the communist society. Pointing, equally, to the relative independence of the consciousness in relation to the pressure of the contradictions of the capital by its revolutionary configuration, Marx would explicit, yet, the possibility of the desired social revolution to be accelerated by the unveiling of the laws of the capital, and this, since the objectives conditions of the revolution are formed, what makes possible the comprehension of The Capital and its way of exposition as a political instrument directed to the organization to the working class, stronger position, including by the knowledge of the revolutionary impetus of Marx and of his political relation with the referred class. On this way, it can be understood the exposition that parts from the abstract to the concrete, or from the part to the whole, providing, on this process, an appropriate comprehension of the way of the capitalist production, which shows the transitory nature of capital; which overcomes, gradually, the illusions on the workers consciousness; which points to the violence of the class struggle as a foundation of the way of the capitalist production and for its revolutionary overcome as the only solution for all the problems faced by the working class, such as the hyper-exploitation of labor, the unemployment and the misery caused by the economic crisis, as an intentional way to awaken the revolutionary consciousness of the working class, motivating, on this way, its political organization.